Bearing thinking of edge computing based on NFV - Yujia LUO; Liang OU; Hong TANG (Dianxin kexue)
Aiming at introducing edge computing into operator’s network,a bearing and deployment thinking based on NFV was presented.Firstly,the industry development trends of edge computing were introduced.Then the concept,service scenarios and special requirements of edge computing were described,as well as the relationship between edge computing and NFV.Then,a bearing thinking of edge computing based on NFV was provided.Furthermore,some preliminary discussions about deploying edge computing platform on operator’s network were offered.Techni cal reference foRthe future deployment of edge computing was provided.